2017
DOI: 10.4028/www.scientific.net/msf.890.396
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Delaying Addition of Heat Stimulated Superplasticizer on Fresh Properties of Mortar

Abstract: To assure the quality and required workability of mortar or concrete, various types of superplasticizers are used. There are many factors affecting the performance of superplasticizers explicitly, type and dosage of the superplasticizers, type of cement, temperature and mixing procedure, as well as the addition times of the superplasticizers. Some researchers investigated the effect of delaying the addition time of superplasticizer to mortar or concrete, but there is not enough data about the effect of externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…There result concluded to estimate that polymer relax and straighten by thermal stimulation. Moreover, in previous studies [7]- [10], when the more contained amount of slump keeping polymer, it was recognized that the polymer was relaxing for thermal stimulation. However, it is thought that by cooled slowly it will return to the size and geometric structure of stable polymer molecules in the state before thermal stimulation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There result concluded to estimate that polymer relax and straighten by thermal stimulation. Moreover, in previous studies [7]- [10], when the more contained amount of slump keeping polymer, it was recognized that the polymer was relaxing for thermal stimulation. However, it is thought that by cooled slowly it will return to the size and geometric structure of stable polymer molecules in the state before thermal stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…As these results, it was confirmed that the effect of thermal stimulation and its sustainability will be improved as the content of SK type in the superplasticizer increases. In the previous studies [7][8][9][10], only fluidity of the mortar right after mixing were investigated, in this study, the effect of thermal stimulation after mixing had been evaluated. Moreover, it was confirmed that even if the initial dispersion performance improves by thermal stimulation, slump keeping performance can be maintained.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations